Comparing the Efficacy and Safety of Glucagon-Like Peptide 1 Receptor Agonists with Sodium-Glucose Cotransporter 2 Inhibitors for Obese Type 2 Diabetes Patients Uncontrolled on Metformin: A Systematic Review and Meta-Analysis of Randomized Clinical Trials - Lu Ding; Bang Sun; Xinhua Xiao (International Journal of Endocrinology)
Introduction. To conduct the first meta-analysis of randomized controlled trials (RCTs) comparing glucagon-like peptide 1 receptor agonists (GLP-1RAs) with sodium-glucose cotransporter 2 inhibitors (SGLT-2is) for obese type 2 diabetes (T2D) patients uncontrolled on metformin. Methods. We searched Pubmed, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), Ovid, and Web of Science from inception to May 14, 2020, without language restrictions for eligible RCTs. The primary outcome is the mean change from baseline in glycated haemoglobin (HbA1c). Results. Totally, 3 RCTs enrolled 2066 patients were identified. Compared with SGLT-2is, treatment with GLP-1RAs achieved significant reduced HbA1c by 0.40% (95% CI: −0.54, −0.25; p<0.00001), fasting blood glucose (FBG) by 0.17 mmol/L (95% CI: −0.31, −0.04; p=0.01), and postprandial blood glucose (PBG) by 0.32 mmol/L (95% CI: −0.49, −0.14; p=0.0003) for obese T2D patients uncontrolled on metformin. The significant benefit of weight loss was seen in semaglutide (MD: −0.75; 95% CI: −1.18, −0.31; p<0.0007). No significant difference was detected between GLP-1RAs and SGLT-2is in overall adverse events (RR: 1.03; 95% CI: 0.98, 1.09; p=0.76), but gastrointestinal events showed higher occurrence in GLP-1RAs groups compared with SGLT-2is (RR: 1.62; 95% CI: 1.37, 1.93; p<0.00001). Subgroup analyses revealed that follow-up time did not statistically influence glycemic control. Conclusion. GLP-1RAs are superior to SGLT-2is for obese T2D patients uncontrolled on metformin in glycemic control without an increase in adverse events except for a higher occurrence in gastrointestinal events. Future large longer-term follow-up clinical trials are needed to provide more evidence about the sustainable effects and safety of GLP-1RAs compared with SGLT-2is.